1980
DOI: 10.2134/jeq1980.00472425000900040032x
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Arsenite by Aquatic Sediments

Abstract: Sediments from five lakes in southern Saskatchewan, Canada, oxidize As(III) (arsenite) to As(V) (arsenate). The oxidation is not affected by flushing N2 or air through the sediment suspensions, nor does the addition of HgCl2 to the system eliminate the conversion of As(III) to As(V). The oxidation is an abiotic process with microorganisms playing a relatively minor role in this system. Because As(III) is more toxic and sorbed to a lesser extent by sediments than As(V), the suspended and bottom sediments may po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 0 publications
6
72
0
1
Order By: Relevance
“…It has been pointed out that manganese (III/IV) oxide particles in natural waters participate in a number of oxidation reactions involving both organic and inorganic com-pounds, increasing the mobility of manganese and its availability to organisms. Although the reduction reactions occurring at the manganese oxide/water interface have received considerable attention for many years (Stone and Morgan, 1984a,b;Oscarson et al, 1980), the oxidation of organic pollutants at the natural manganese mineral surface as a degradable pathway is poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been pointed out that manganese (III/IV) oxide particles in natural waters participate in a number of oxidation reactions involving both organic and inorganic com-pounds, increasing the mobility of manganese and its availability to organisms. Although the reduction reactions occurring at the manganese oxide/water interface have received considerable attention for many years (Stone and Morgan, 1984a,b;Oscarson et al, 1980), the oxidation of organic pollutants at the natural manganese mineral surface as a degradable pathway is poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of As(III) to As(V) by manganese oxide minerals is an important means of altering the toxicity of arsenic in aquatic environments (Oscarson et al, 1980(Oscarson et al, , 1981a(Oscarson et al, , 1981b(Oscarson et al, , 1983. As common particulates in fresh and marine environments, various forms of manganese oxides mediate these reactions (Jenne, 1968;Murray, 1975;Martin and Meybeck, 1979;Wangersky, 1986;Lind, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…As common particulates in fresh and marine environments, various forms of manganese oxides mediate these reactions (Jenne, 1968;Murray, 1975;Martin and Meybeck, 1979;Wangersky, 1986;Lind, 1988). Birnessite, a frequently encountered, natural form of manganese oxide in modern sediments and soils (Jones and Milne, 1956;Giovanoli et al, 1970a), is an important component in the natural oxidation of As(III) to As(V) (Oscarson et al, 1980). Because As(III) is more toxic than As(V) (Coddington, 1986), this reaction controls arsenic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier Oscarson et al (1980) reported the abiotic oxidation of As(Ill) to As(V) by freshwater lake sediments. Here evidence is presented indicating that Mn is the primary sediment component responsible for the oxidation of As(III) to As(V).…”
Section: Introductionmentioning
confidence: 99%